Exploring the role of theatre in empowering children: The case of Baba Watoto Centre in Dar es salaam, Tanzania - Edward, Sophia (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Development Policy (MSc. DP) of Mzumbe University